2014
DOI: 10.1111/add.12666
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between years of cocaine use and brain activation to cocaine and response inhibition cues

Abstract: Aims Functional Magnetic Resonance Imaging research has attempted to elucidate the neurobehavioral underpinnings of cocaine dependence by evaluating differences in brain activation to cocaine and response inhibition cues between cocaine dependent individuals and controls. Less research has investigated associations between task-related brain activation and cocaine use characteristics; the present study was designed to address this gap in the literature. Design Cross-sectional. Setting The Center for Brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…In addition, these results are also consistent with those from a previous study investigating tryptophan depletion in humans while performing the continuous performance task [40]. Voon et al [39] found that, compared to healthy volunteers, cannabis users, tobacco smokers, and those dependent on either alcohol or methamphetamine showed increased premature responding, consistent with other studies which investigated impulsive action using GNG tasks in groups abusing heroin [41], cocaine [42, 43] [44], and tobacco [45], particularly during deprivation [46]. …”
Section: Underlying Neurocircuitry Of Impulsivitiessupporting
confidence: 88%
“…In addition, these results are also consistent with those from a previous study investigating tryptophan depletion in humans while performing the continuous performance task [40]. Voon et al [39] found that, compared to healthy volunteers, cannabis users, tobacco smokers, and those dependent on either alcohol or methamphetamine showed increased premature responding, consistent with other studies which investigated impulsive action using GNG tasks in groups abusing heroin [41], cocaine [42, 43] [44], and tobacco [45], particularly during deprivation [46]. …”
Section: Underlying Neurocircuitry Of Impulsivitiessupporting
confidence: 88%
“…Secondary analyses were conducted to evaluate the relationship between some potential factors that have been identified as contributors to the intensity of craving in human studies (1, 2, 4, 22) and patterns of cue-associated brain activation. The correlation analyses (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo recording studies show that the frequency of reactivation is highest in the minutes following (Kudrimoti et al, 1999;Tatsuno et al, 2006) but may persist for 18 -24 h (Kudrimoti et al, 1999;Karlsson and Frank, 2009) after an experience. Although largely studied in hippocampus and cortex, postencoding reactivation has also been described in other brain regions (Pennartz et al, 2004) and may represent a ubiquitous phenomenon. For instance, Johnson et al (2009) observed that stimulation of the LA produced polysynaptic field potentials, consistent with the idea that reverberatory activity or reactivation may also occur in LA microcircuits.…”
Section: Consolidation Of a Cocaine-cue Memory Is Disrupted By Posttrmentioning
confidence: 99%
“…For instance, lesioning (Fuchs et al, 2002) or disrupting synaptic plasticity (Heldt et al, 2014) in the lateral/basolateral amygdala region in rodents, impairs the acquisition of cocaine-conditioned place preference (CPP), in which an initially neutral environmental cue is paired with cocaine administration. Moreover, functional magnetic resonance imaging (fMRI) data from humans with a history of cocaine use shows that presentation of cues previously associated with cocaine not only induce craving but increase activation in a number of brain regions, including the amygdala (Chase et al, 2011;Prisciandaro et al, 2014). Together, these findings indicate that the amygdala may play an important role in the formation and expression of cocaine-cue memories that are relevant for addiction.…”
Section: Introductionmentioning
confidence: 99%